The Subject Position and Network Entrepreneurship of Parent Organizations in China. - Huang, Shixin; Chen, Yonghai; Zhou, Lingang (China Quarterly, 2025)
Since the 1990s, Chinese parents of people with intellectual and developmental disabilities (PWIDD) have been founding rehabilitation service non-governmental organizations (NGOs) to fill the social welfare gaps in disability services in their local areas. More recently, however, a new form of mutual aid organization – the parent organization, which focuses on family empowerment and advocacy – has emerged and diffused trans-locally, along with two national networks' organizational incubation initiatives. Following an institutional approach to organizational studies and drawing on ethnographic fieldwork conducted between 2019 to 2023, this study traces the trans-local expansion of this novel organizational form in the emerging field of Chinese NGOs. We argue that parent organizations strategically orchestrate a form of institutional work – network entrepreneurship – characterized by three organizational processes: vertical connections between national networks and local member organizations, horizontal interactions among senior and new parent organizers, and the creative translation and adaptation of local parent organizations. Together, these three processes facilitate the trans-local diffusion of organizational resources, identity, ideas and practices. The findings make theoretical contributions by highlighting the institutional implications of peer organization networks, especially through the emerging subject position of "parent of PWIDD," in the incubation and diffusion of a novel organizational form trans-locally.